Deacetylases and NF-κB in Redox Regulation of Cigarette Smoke induced Lung Inflammation: Implications in Pathogenesis of COPD - Rajendrasozhan, Saravanan (2008)
Oxidative stress has been implicated in the pathogenesis of several inflammatory lung disorders including chronic obstructive pulmonary disease (COPD) due to its effect on pro-inflammatory gene transcription. Cigarette smoke-mediated oxidative stress activates NF-κB-dependent transcription of pro-inflammatory mediators either through activation of inhibitor κB-α kinase (IKK) and/or the enhanced recruitment and activation of transcriptional co-activators. Enhanced NF-κB-co-activator complex formation results in targeted increase in chromatin modifications, such as histone acetylation leading to inflammatory gene transcription. NF-κB-dependent gene expression, at least in part, is regulated by changes in deacetylases such as histone deacetylases (HDACs) and sirtuins. Cigarette smoke and oxidants also alter the levels/activity of HDAC by post-translational modifications and in doing so further induces gene expression of pro-inflammatory mediators. In addition, cigarette smoke/oxidants can reduce glucocorticoid sensitivity by attenuating HDAC2 activity and expression, which may account for the glucocorticoid insensitivity in patients with COPD. Understanding the mechanisms of NF-κB regulation, and the balance between histone acetylation and deacetylation may lead to the development of novel therapies based on the pharmacological manipulation of IKK and deacetylases in lung inflammation and injury.